Transformational Leadership: The Principal’s Efforts in Enhancing Teacher Professionalism at Al-Husna Islamic Boarding School, Marendal - Faid Ali (Sufiya Journal of Islamic Studies, 2024)
Principal leadership plays a strategic role in directing and fostering teachers to be more professional in carrying out educational duties. This research uses a qualitative approach with a case study type, which is conducted through field observations, in-depth interviews with the head of the pesantren and teachers, and documentation of activities at the Al-Husna Marindal Islamic Boarding School. In addition to primary data, secondary data from various scientific sources such as journals, books, and other scientific works were also used. Data were analyzed through the process of data reduction, data presentation, and conclusion drawing. The results show that the principal plays an important role as a transformational leader who not only develops the vision and mission, but also actively motivates teachers through regular coaching, job evaluation, and rewarding. This leadership approach succeeded in improving teachers' morale, creativity in teaching, and the quality of interaction in the learning process. This finding confirms that the transformational leadership style applied consistently and contextually is able to build a collaborative work climate, encourage the improvement of teacher professionalism, and strengthen the role of Islamic boarding schools as educational centers that are responsive to the challenges of the times.